Stock Prices in Nepal: Macroeconomic Determinants - Ojha, Bhoj Raj (Management Dynamics, 2021)
The article attempts to identify the relationship between major determinants and its impact of stock market of Nepal. On employing, Regression Analysis on data set for the period of 1994-2020, it is found that there is significant relation between determinants of stock market and stock price. The findings imply that stock market price fluctuations are closely related to broad money supply, interest rate, inflation, and exchange rate in the long run. The fluctuation of stock market prices in relation to interest rates is in the opposite direction. In the short run, GDP, money supply, and exchange rate all have positive relationships, but only the money supply has a positive relationship in the long run. Stock market prices rise as the money supply expands. This implies that an increase in money supply leads to economic expansion through increasing cash flows, and that an expansionary monetary policy would help stock values. Capital market development strategies should be coordinated with macroeconomic fundamental policies.